THE DANGERS OF TRANSNATIONAL IDEOLOGY IN INDONESIA: THREATS TO SOCIAL STABILITY AND DIVERSITY - Yuliana Sulistyaningtyas; Fauzia Nur Aeni; Choiril Anwar; Qomariyah (Jurnal Ikhtibar Nusantara, 2025)
This study aims to analyze the impact and threats of transnational ideology on social stability and diversity in Indonesia. The method used is a qualitative method with a descriptive approach, which relies on secondary data from various literature and written publications. Transnational ideology that crosses national borders is understood as a global understanding that can influence a nation's political policies and local values . In Indonesia, the spread of this transnational ideology often conflicts with Pancasila and cultural values, thus triggering radicalization, tension between groups, decreased tolerance, and the potential for social disintegration. The results of this study indicate that transnational ideology has a significant impact on social stability, such as social division and radicalization, tension between groups with different ideological values, and decreased tolerance and cultural diversity. This potential for social disintegration is a grave concern. Where this is spread through social media which is used to spread propaganda and intolerant narratives to the Indonesian people, to overcome the impact of this threat the Indonesian government has implemented various strategies, such as the establishment of the Pancasila Ideology Development Agency (BPIP), education of Pancasila values, law enforcement against radical groups, strengthening cyber, and international cooperation.